ASCAR toolkit V2 / Amirul Hakimi Azmi … [et al.] - Azmi, Amirul Hakimi; Murtadza, Amalea; Mohd Yusof, Mohd Idham; Makhtar, Muhammad Qayyum; Noor Azam, Zulaikha (Division of Research and Industry Linkages, 2017)
ASCAR TOOLKIT V2 is an innovation pioneered by the students association under the Faculty of Administrative Science and Policy Studies (FSPPP). This product is an output resulted from the FSPPP students conferences organised in UiTM Seremban campus after FSPPP successfully organised its maiden student’s carnival called Administrative Science Carnival (ASCAR) 2016. This project is a toolkit that will assist the organiser in organising ASCAR as it will be an annual event for the faculty. This product will be used by the students association in campuses that offering programmes offered by FSPPP to have a standardised system for handling the ASCAR programme. It will be the trademark for the faculty, one of the oldest in UiTM. This product will be able to guide the organiser to have systematic and efficient programmes that will generate income for the faculty and student society. In future this product will be improved through establishment of necessary system or database that may support the implementation of ASCAR. It will also hope to be a guideline for other students association in the other faculty in organising a large carnival.